Feasibility of Using High-Performance Steel Fibre Reinforced Concrete for Simplifying Reinforcement Details of Critical Members - Seok-Joon Jang; Dae-Hyun Kang; Kyung-Lim Ahn; Wan-Shin Park; Sun-Woong Kim; Hyun-Do Yun (International Journal of Polymer Science)
This paper addresses the effects of hooked-end steel fibre contents on the mechanical properties of high-performance concrete (HPC) and investigates the feasibility of utilizing steel fibres to simplify the complicated reinforcement detailing of critical HPC members under high shear stress. Mechanical properties of HPCs with specified compressive strength of 60 and 100 MPa include the flow, air content, compressive strength, and flexural strength. The effectiveness of 1.50% steel fibre content on the shear behaviour of diagonally reinforced concrete coupling beam without additional transverse reinforcement was investigated to alleviate complex reinforcing details for the full section confinement of diagonal bar groups. The test results revealed the incorporation of steel fibres significantly affected the mechanical properties of the HPCs. For diagonally reinforced coupling beam (SFRCCB) without additional transverse reinforcement, the addition of 1.5% steel fibre content into 60 MPa HPC coupling beam provides similar cracking and structural behaviours compared to those of diagonally reinforced coupling beam (CCB) with full section confinement details. However, the ductility of SFRCCB was less than that of CCB. It is recommended that both stirrups and steel fibre should be used for fully confining the diagonal bar groups of coupling beams to achieve the ductile behaviour.